2019
DOI: 10.33373/mja.v13i1.1855
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Anggaran, Budget Emphasis Dan Self Esteem Terhadap Budgetary Slack Pada Hotel Berbintang Empat Di Kota Batam

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh pengaruh partisipasi anggaran, Budget Emphasis, dan Self Esteem  terhadap Budgetary Slack pada hotel berbintang empat di kota Batam. Penelitian ini dilakukan dihotel berbintang empat di kota batam. Metode yang digunakan dalam penelitian ini adalah metode teknik survei dengan menyebarkan kuesioner langsung kepada responden (karyawan) pada masing-masing hotel tempat dimana responden bekerja.Berdasarkan hasil penelitian, analisis partisipasi anggaran terh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…During the budgeting process, positive communication between superiors and allows superiors to acquire access to subordinates' confidential information, which in turn allows them to design better budget-achievement tactics, therefore, has a negative effect to create slack (Baccouri & Hassouna, 2017;Hassan et al, 2011;Kren, 2003). A direct positive link between environmental uncertainty and the inclination to produce slack was discovered to have the greatest effect on the propensity to create slack (Huseno, 2017;Kepramareni et al, 2020) Contrary, the result studies of Arista & Syofyan (2019b); Hati (2019); Hutama & Yudianto (2019); and Kepramareni et al (2020) suggested that budgeting participation has a positive effect on budgetary slack. During the budgeting process, communication could be a positive effect on budgetary slack because the party who knows information better is motivated to create budget slack by misrepresenting or concealing part of their private knowledge (Kepramareni et al, 2019;Yuen, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…During the budgeting process, positive communication between superiors and allows superiors to acquire access to subordinates' confidential information, which in turn allows them to design better budget-achievement tactics, therefore, has a negative effect to create slack (Baccouri & Hassouna, 2017;Hassan et al, 2011;Kren, 2003). A direct positive link between environmental uncertainty and the inclination to produce slack was discovered to have the greatest effect on the propensity to create slack (Huseno, 2017;Kepramareni et al, 2020) Contrary, the result studies of Arista & Syofyan (2019b); Hati (2019); Hutama & Yudianto (2019); and Kepramareni et al (2020) suggested that budgeting participation has a positive effect on budgetary slack. During the budgeting process, communication could be a positive effect on budgetary slack because the party who knows information better is motivated to create budget slack by misrepresenting or concealing part of their private knowledge (Kepramareni et al, 2019;Yuen, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…However, the results of a study conducted by (Arista & Syofyan, 2019b;Hati, 2019;Hutama & Yudianto, 2019;Kepramareni et al, 2020;Yuen, 2004) stated that budgeting participation has a positive effect on the budgetary slack. This means that budgetary participation increases the propensity to create budgetary slack.…”
Section: Budgeting Participationmentioning
confidence: 99%
See 3 more Smart Citations